Comparison of electrocardiogram diagnostic criteria in diagnosis of left ventricular hypertrophy using 3D echocardiography as standard - Mathur, Rohit; Pawan Sarda; Anil Baroopal; Pankaj Kumar; Abhishek Sakwaria (International Journal of Research in Medical Sciences, 2023)
Background: The echocardiogram (ECHO) has a better diagnostic performance for left ventricular hypertrophy (LVH) than the electrocardiogram (ECG), but ECG is most widely used diagnostic method. We aimed to assess the correlation between ECG based diagnosis of LVH with echocardiography-based diagnosis of LVH as standard. Methods: Patients with evidence of LVH using echocardiographic criteria were included in the study. Patients were subjected to four electrocardiographic criteria to assess the LVH: 1. Sokolow-Lyon criteria; 2. Romhilt and Estes scoring system; 3. Cornell voltage criteria; and 4. Gubner voltage criteria. After assessing the results of ECG and echocardiography diagnostic validity tests (by calculating specificity and sensitivity), the Kappa measure of agreement was performed. Results: In maximum patients (52.8%) LVH was detected by using ECG LVH Sokolow Lyon criteria, followed by Cornell voltage CR criteria that detected LVH in 38.9% cases. Sokolow Lyon ECG criteria showed high sensitivity while Romhilt and Estes criteria showed maximum 98% specificity in diagnosing LVH. Sokolow Lyon’s ECG criteria was highly sensitive in assessing all co-morbidities, except CKD where it was diagnosed better by using Cornell voltage criteria. Conclusions: In cases of diagnosing LVH in patients with co-morbidities, ECG LVH Sokolow Lyon CR was found to be the most sensitive criteria except CKD where it was diagnosed better by using Cornell voltage criteria. For assessing the patients for LVH, the role of ECG with all the commonly used criteria is of limited value and ECHO should be the method of choice.